Mnemofunctions and some of their applications - Antonevič, A. B.; Radino, N. J.; Radino, J. V. (Mathematical Modelling and Analysis, 1996)
“Мнемофункции и некоторые их приложения”Mathematical Modelling Analysis, 1(1), p. 7-14.Article in Russian.First Published Online: 14 Oct 2010